Estimating regions of interest on the distal femur. (October 2018) - van der Merwe, Johan; van den Heever, Dawie J.; Erasmus, Pieter J.
Highlights: A shape model is used to estimate unknown femoral condylar regions. Estimations are validated via both surface and local metrics. Model shows good results for medial and lateral condyles. Applications include patient-specific knee implant design. Graphical abstract: Abstract: We investigated the ability of a statistical shape model to estimate unknown regions of interest related to patient-specific unicompartmental knee replacement design on the distal femur. Generality ranged between 0.67 and 1.03 mm, specificity from 0.79 to 1.07 mm, and leave-one-out root mean square estimation errors from 0.88 to 1.27 mm for different regions. Moderate to strong correlations were established between ground truths and model estimates for local morphological measurements on the medial and lateral condyles. Results compared well to similar studies in the literature, and we conclude that shape models might prove useful during patient-specific unicompartmental knee replacement design.